PENGARUH PEMANFAATAN MEDIA SOSIAL WHATSAPP TERHADAP PENYAMPAIAN PESAN DI ANGKATAN MUDA RANTING II CABANG BETHEL - MARLEEN MUSKITA (Fakultas Ilmu Sosial dan Ilmu Politik, 2019)
Social media is an online media, with its users can easily participate, share, and create blog content, social networks, wikis, forums and virtual worlds. This research was conducted to determine the extent of the influence of the use of Whatsapp social media as a medium for delivering messages in the Second Branch of AMGPM. The purpose of this research is to find out and analyze the influence of the use of whatsapp and facebook applications on religious organizations. This research uses a qualitative approach with the type of research used is a descriptive approach. The use of WhatsApp social media has an effect on the dissemination of information in AMGPM Twig II Bethel Branch. WhatsApp features that can be used to disseminate learning information include Chat Groups, photos, videos, voice messages and documents. The use of whatsapp is very effective in conveying messages to AMGPM Branch II, because the messages conveyed get more responses from the whatsapp group.